The Correlation Between Community Knowledge Level on Nutritional Intake and the Incidence of Type 2 Diabetes Mellitus in the Working Area of Sukodono Public Health Center - Rosyidin, Azharine Mushfira Nur; Maimuna, Siti; Hilmi M., M. Afif; Widarti, Luluk (Global Ten Public Health and Nursing Journal, 2025)
Type 2 diabetes mellitus (DM) is a chronic disease whose incidence is constantly increasing, often caused by a lack of knowledge about proper nutritional intake. The goal is to investigate the relationship between public knowledge about nutritional intake and the emergence of type 2 diabetes mellitus in the Sukodono Health Center area. Observation of correlation analysis using a cross-sectional approach. A total of 55 patients were collected using the simple random sampling method to be used as a sample. Nutritional intake knowledge questionnaires as well as blood sugar checks during fasting were used for data collection. Data analysis in this study used the chi-square test. While patients with low knowledge had fasting glucose levels showing unmanaged spikes, reaching a figure of about 63.6%, those who understood the condition of diabetes well were generally better able to maintain the stability of glucose levels in their bodies. Knowledge of nutrient intake and the incidence of type 2 diabetes showed a relevant and significant correlation (p=0.019). Health education related to nutritional intake has proven to be important in the management and prevention of complications of diabetes mellitus. Improving education and health interventions is a crucial step to reduce the incidence of type 2 DM.